2001
DOI: 10.1055/s-2001-17157
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Traumatic Injuries of the Gastrointestinal and Biliary Tract in Childhood. Analysis of 16 Cases

Abstract: Incidence of blunt hollow viscus injuries is low in children. Hematomas are easily recognized by modern radiography, and simply managed nonoperatively. Diagnosis of perforations still remains difficult. This results in dangerous delays for lesions which need prompt repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…followed 19 children for 10 years and 21 children for 19 years and found only one duodenal hematoma after abdominal blunt trauma in each series (2). Galifer et al (3) studied pediatric blunt trauma for seven years and found 16 cases of gastrointestinal damage with only one case with gall bladder complications. Lin (4) reported a ten year-old girl with biliary emesis after abdominal blunt trauma,diagnosed with duodenal hematoma, managed nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…followed 19 children for 10 years and 21 children for 19 years and found only one duodenal hematoma after abdominal blunt trauma in each series (2). Galifer et al (3) studied pediatric blunt trauma for seven years and found 16 cases of gastrointestinal damage with only one case with gall bladder complications. Lin (4) reported a ten year-old girl with biliary emesis after abdominal blunt trauma,diagnosed with duodenal hematoma, managed nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Die Läsion ist häufig nicht radiologisch darstellbar, daher werden indirekte Zeichen wie freie Luft im Bauchraum im Röntgenbild sowie Darmwand-Enhancement oder intramurale Luft zur Diagnosestellung herangezogen. Dennoch wird die Diagnosestellung als schwierig eingeschätzt, und betroffene Patienten fallen erst im Verlauf durch persistierende abdominelle Schmerzen und Peritonitis auf [14]. Die konservative Therapie ist ausschließlich bei erstgradigen Verletzungen ohne Perforation des Hohlorgans mög-lich.…”
Section: Hohlorganverletzungenunclassified
“…Je nach Allgemeinzustand des Patienten und Begleitverletzungen kann eine Laparoskopie erwogen werden. Intraoperativ richtet sich das Vorgehen nach dem Befund und kann variieren zwischen einer isolierten Darmnaht, Segmentresektion mit Anastomose oder der Anuspraeter-Anlage [2,7,14].…”
Section: Hohlorganverletzungenunclassified
“…U našoj studiji povrede 'eluca i duodenuma su bile udru'ene sa povredama mnogih organa i vaskularnih struktura u trbuhu, tako da nije bilo ni jedne izolovane povrede. Naša iskustva su sli~na sa iskustvima svetskih centara objavljenih u literaturi 3,8,11 . Udru'enost povreda je svakako uticala na te'inu stanja naših pacijenata, stepena iskrvarenja i morbiditet, tako da je i pristup u le~enju povredjenih bio vrlo kompleksan i uklju~ivao ~itav tim specijalista.…”
Section: Diskusijaunclassified